Epidemiological and clinical study of leishmaniasis in Kirkuk city, Iraq - Obaid, Hiro M.; Shareef, Hager A. (Iraqi Journal of Science, 2018)
leishmaniasis is a disease of global concern, Leishmania types and distribution rates vary from country to another. For visceral leishmaniasis serum samples were examined by the kala-azar dipstick rapid test. Meanwhile smears were taken from lesions, air dried, fixed and Leishman stained then microscopically examined for amstigote stage in cutaneous leishmaniasis. From April 2014 to April 2015, 150 samples for cutaneous leishmaniasis (CL) and 108 serum sample for visceral leishmaniasis (VL) from in and out patients in Pediatric, Azadi Teaching and Kirkuk General Hospitals were examined. The incidence of visceral leishmaniasis was very low (2.7%) comparing to that in cutaneous leishmaniasis (64.6%). No significant differences had appeared between the cutaneous leishmaniasis incidence in male or female. The most age group infected with cutaneous leishmaniasis in both genders was 5 ≤ years old, with rate of 26.1% in male and a rate of 15.8% in female. Significantly high frequency of the patients were presented with only one or two lesions with rate of 39.17, 25.7 % for each type of lesions respectively. The most location that infected with CL was hand (27.7%) and high rate of them being moist type (71.13%). In Kirkuk city CL is more prevalent than VL. High rate of CL is moist type locating in the limbs and face. The infection is more frequent in children than in adult. For CL a smear taken from the lesion is much worthy than a lesion blood sample or re aspirated saline injected to the lesion.